2021
DOI: 10.17712/nsj.2021.3.20210077
|View full text |Cite
|
Sign up to set email alerts
|

Treatable inherited metabolic epilepsies

Abstract: Inherited metabolic diseases usually present a complex clinical picture in which seizures are one of various neurological manifestations, which include developmental delays/regression, acute encephalopathy, neuropsychiatric manifestations, and movement disorders. However, a seizure can be the prominent feature in inherited metabolic disease. The specific diagnosis of an underlying inherited metabolic disorder in epileptic patients may help design specific treatments that can improve the seizures and stop neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Extensive research has demonstrated that intractable epilepsy is caused by numerous precipitating factors and can produce a great impact on the cognitive mental, psychological, and social functions of childhood with epilepsy (Hwang et al 2019). Seizures might be the prominent feature in inherited metabolic disease (Hundallah and Tabarki 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has demonstrated that intractable epilepsy is caused by numerous precipitating factors and can produce a great impact on the cognitive mental, psychological, and social functions of childhood with epilepsy (Hwang et al 2019). Seizures might be the prominent feature in inherited metabolic disease (Hundallah and Tabarki 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, most seizures in newborns are often classified as acute symptomatic seizures and are usually due to a brain injury [ 14 ]. In contrast, neonatal-onset epilepsies are reported in ~12% of newborns with seizures and can be associated with genetic mutations [ 15 , 16 , 17 , 18 , 19 ], brain malformations [ 20 , 21 ], and metabolic disorders [ 22 , 23 ]. Model organisms that are amendable to genetic manipulations, brain imaging, and high-throughput screening of new compounds are critical for discovery of new therapeutics with different properties.…”
Section: Introductionmentioning
confidence: 99%